Hierarchical Fixed Point Problems in Uniformly Smooth Banach Spaces - Lu-Chuan Ceng; Ching-Feng Wen; Chin-Tzong Pang (Abstract and Applied Analysis, 2014)
We propose some relaxed implicit and explicit viscosity approximation methods for hierarchical fixed point problems for a countable family of nonexpansive mappings in uniformly smooth Banach spaces. These relaxed viscosity approximation methods are based on the well-known viscosity approximation method and hybrid steepest-descent method. We obtain some strong convergence theorems under mild conditions.